2021
DOI: 10.1073/pnas.2105328118
|View full text |Cite
|
Sign up to set email alerts
|

On the microstructural origin of brain white matter hydraulic permeability

Abstract: Brain microstructure plays a key role in driving the transport of drug molecules directly administered to the brain tissue, as in Convection-Enhanced Delivery procedures. The proposed research analyzes the hydraulic permeability of two white matter (WM) areas (corpus callosum and fornix) whose three-dimensional microstructure was reconstructed starting from the acquisition of electron microscopy images. We cut the two volumes with 20 equally spaced planes distributed along two perpendicular directions, and, on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 41 publications
(15 reference statements)
0
12
0
Order By: Relevance
“…Furthermore, the geometry of axon was also simplified. The mathematical model in this paper can be combined with realistic brain microstructure reconstructed from microscopic images (Bernardini et al 2021;Vidotto et al 2021) to further improve the model accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the geometry of axon was also simplified. The mathematical model in this paper can be combined with realistic brain microstructure reconstructed from microscopic images (Bernardini et al 2021;Vidotto et al 2021) to further improve the model accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Biomechanically, it can be broadly characterised by the stiff directional axons wrapped in insulating lipid-rich layers (myelin) that are supported by a soft matrix composed of glial cells and a network of biopolymers, the extracellular matrix (ECM). The directional axons can be a mechanical obstacle to drug diffusion and spatial distribution in the CNS tissue [ 18 , 19 ]. The presence of elongated axons can compel the drug particles to diffuse around fibre-like obstructions, hence the increased tortuosity and reduced effective diffusion.…”
Section: Brain Tissue: a Complex System For Diffusion-based Drug Deli...mentioning
confidence: 99%
“…Only a recent study on fixed tissue of sheep brain has revealed localised microstructural differences such as axon volume fractions and geometry in specific regions, i.e., the corpus callosum, corona radiata and fornix of CNS [ 58 ]. Appreciating this fact, Vidotto et al [ 19 ] used a computational approach and found a significant difference between hydraulic permeability in the corpus callosum and fornix. Using 3D reconstructed microstructure from electron microscopy images, they computed the corresponding permeability considering the tissue structure is mainly composed of directional axons.…”
Section: Infusion-based Drug Delivery In Cns Tissuementioning
confidence: 99%
See 2 more Smart Citations